Regularizing Inverse Preconditioners for Symmetric Band Toeplitz Matrices. (30th April 2007) - Favati Favati, P. P.; Lotti Lotti, G. G.; Menchi Menchi, O. O.
Abstract : Image restoration is a widely studied discrete ill-posed problem. Among the many regularization methods used for treating the problem, iterative methods have been shown to be effective. In this paper, we consider the case of a blurring function defined by space invariant and band-limited PSF, modeled by a linear system that has a band block Toeplitz structure with band Toeplitz blocks. In order to reduce the number of iterations required to obtain acceptable reconstructions, in 13 an inverse Toeplitz preconditioner for problems with a Toeplitz structure was proposed. The cost per iteration is ofO ( n 2 log n ) operations, wheren 2 is the pixel number of the 2D image. In this paper, we propose inverse preconditioners with a band Toeplitz structure, which lower the cost toO ( n 2 ) and in experiments showed the same speed of convergence and reconstruction efficiency as the inverse Toeplitz preconditioner.